A WLAN triage testbed based on fuzzy logic and its performance evaluation for different number of clients and throughput parameter. (2019) - Ozera, Kosuke; Inaba, Takaaki; Bylykbashi, Kevin; Sakamoto, Shinji; Ikeda, Makoto; Barolli, Leonard
Many devices communicate over Wireless Local Area Networks (WLANs). The IEEE 802.11e standard for WLANs is an important extension of the IEEE 802.11 standard focusing on Quality of Service (QoS) that works with any PHY implementation. The IEEE 802.11e standard introduces Enhanced Distributed Channel Access (EDCA) and HCF Controlled Channel Access (HCCA). Both these schemes are useful for QoS provisioning to support delay-sensitive voice and video applications. EDCF uses the contention window to differentiate high-priority and low-priority services. However, it does not consider the priority of users. In this paper, in order to deal with this problem, we propose a Fuzzy-based Admission Control System (FACS). We implemented a triage testbed using FACS and carried out an experiment. The experimental results show that the number of connected clients is increased during Avoid phase, but does not change during Monitoring phase. The experimental results show that the implemented testbed performs better than conventional WLAN.